2022
DOI: 10.32872/cpe.6821
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy under lockdown: The use and experience of teleconsultation by psychotherapists during the first wave of the COVID-19 pandemic

Abstract: Background Facing the COVID-19 pandemic, some psychotherapists had to propose remote consultations, i.e., teleconsultation. While some evidence suggests positive outcomes from teleconsultation, professionals still hold negative beliefs towards it. Additionally, no rigorous and integrative practice framework for teleconsultation has yet been developed. This article aims to explore the use and experience of teleconsultation by 1) investigating differences between psychotherapists proposing and not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…This was also observed by Cantone et al [ 61 ]. Notermans et al [ 62 ] found that interventions that intend to activate intense or aversive feelings are avoided in the setting of remote therapy. Probst et al [ 26 ] also concluded that therapeutic interventions are considered more typical for face-to-face psychotherapy than for psychotherapy at a distance.…”
Section: Discussionmentioning
confidence: 99%
“…This was also observed by Cantone et al [ 61 ]. Notermans et al [ 62 ] found that interventions that intend to activate intense or aversive feelings are avoided in the setting of remote therapy. Probst et al [ 26 ] also concluded that therapeutic interventions are considered more typical for face-to-face psychotherapy than for psychotherapy at a distance.…”
Section: Discussionmentioning
confidence: 99%